Implementation of Anthropometry on the Design of Study Tables and Chairs in Pekanbaru 17 Public Elementary School Students Against the Prevention of Musculoskeletal Disorders (MSD's): Implementasi Antropometri Terhadap Desain Meja Kursi Belajar Pada Siswa Sekolah Dasar Negeri 17 Pekanbaru Terhadap Pencegahan Muskuloskeletal Disorders (MSD’s) - Makomulamin , Makomulamin; Sari, Nila Puspita; Sridefina, Fhuja (Jurnal Pengabdian Kesehatan Komunitas (Journal of Community Health Service), 2022)
Antropometri merupakan studi tentang pengukuran fisik tubuh manusia, mengenai dimensi bentuk serta ukuran tubuh yang dapat digunakan dalam klasifikasi dan perbandingan antropologis. Antropometri digunakan sebagai pertimbangan ergonomis dalam proses perancangan desain produk. Sekolah Dasar Negeri 17  Pekanbaru sudah memiliki meja dan kursi yang jumlahnya cukup sesuai dengan kebutuhan siswanya. Namun, dalam implementasi antropometrinya belum sesuai dengan dimensi tubuh siswa tersebut, ukuran tubuh siswa yang tidak sama dengan ketersediaan meja dan kursi sehingga sangat mengganggu siswa dalam kenyamanan duduk dikelas, terdapat siswa yang merasakan keluhan nyeri punggung ketika mengikuti proses pembelajaran selama dikelas, nyeri pada leher, pergelangan tangan dan bagian tubuh lainnya, hal ini dikarenakan kursi yang tidak sesuai dengan ukuran dimensi tubuh siswa tersebut. Kegiatan  ini bertujuan untuk menganalisis secara antropometri postur tubuh siswa, ketinggian meja belajar dan desain kursi belajar siswa yang ergonomis terhadap pencegahan Muskuloskeletal Disorders. Kegiatan dilakukan dalam bentuk promosi Kesehatan yang diikuti oleh siswa dengan menerapkan protokol kesehatan pada waktu kegiatan tatap muka terbatas disekolah. Metode yang digunakan adalah ceramah dan diskusi dengan peserta penyuluhan dengan luaran kegiatan artikel pengabdian masyarakat. Abstrak Anthropometry is the study of the physical measurements of the human body, regarding the dimensions of body shape and size that can be used in anthropological classification and comparison. Anthropometry is used as one of the ergonomic considerations in the design process. SDN 17 Pekanbaru already has a sufficient number of tables and chairs according to the needs of its students. However, the implementation of anthropometry is not in accordance with the dimensions of the student's body, the size of the student's body that is not the same as the availability of tables and chairs greatly interferes with students sitting comfortably in class. There are students who feel complaints of back pain when participating in the learning process during class, such as pain in the neck, wrist, and other body parts. This is because the chair does not match the dimensions of the student's body. This activity aims to analyze students' posture anthropometry, height and design of ergonomic student desks and chairs for the prevention of Musculoskeletal Disorders. The activity was carried out in the form of counseling which was attended by students by implementing health protocols when face-to-face activities were limited at school. The method used was lectures and discussions with the output of community service article. The results of this activity were known that the design conditions of the tables and chairs were still not in accordance with the dimensions of the student's body shape, causing complaints about disturbances in MSD's. In conclusion, one of the efforts that can be made to avoid MSD's complaints is when students sit, pay attention to their position and how to sit. They should not sit in a bent position, tilt to the left or right, and often do stretching movements